Luttes autochtones pour une éducation autodéterminée : pratiques rebelles au Chiapas - Bruno Baronnet; Richard Stahler-Sholk (IdeAs)
From the context of the struggle of the Zapatista Maya peoples in southern Mexico, this article outlines the sociopolitical issues related to self-determined educational practices arising from the daily struggle of the rebel families in the Lacandon Jungle and the Highlands of Chiapas. Drawing on more than twenty-five years of monitoring, support and analysis, this paper reflects on the challenges of exercising political autonomy in the field of indigenous education, turning away from the Mexican state’s assimilationist ideology of indigenism in favor of a more multilingual, intercultural, integral, critical, and emancipatory learning approach. Furthermore, the autonomous forms of school education for the children of Maya militants are closely linked to democratic modes of collective decision-making within communal and regional assemblies, organized through meetings and councils that deliberate and act at all levels. This study analyzes how the Zapatista movement has made education the foundation of a profound sociocultural transformation, catalyzing knowledge rooted in territories and identities. It also examines the ongoing struggles for self-determined education led by the Zapatista rebels, thirty years after their armed uprising, highlighting the influential changes and international echoes of their self-governance structures.